The Possible Preventive Effect of Thymoquinone on the Hematological Picture in Rabbits in which Colorectal Cancer Was Developed Experimentally (Journal of Hama University, 2026)
The aim of this research was to study the possible protective effect of thymoquinone of plant origin in hepatic enzymes (alanine aminotransferase and aspartate aminotransferase) in rabbits with colorectal cancer.This study was conducted on (36) male rabbits of a domestic breed and at the age of (6-4) months, with an average weight of (1400-1200)g, divided into three groups, each of which includes (12)rabbits, the study groups except the first group (passive control) injected two doses of azoxymethane to induce colorectal tumors, by injection into the peritoneal cavity at a dose of (15mg/kg), with an interval of a week between the two doses, i.e. a dose every week, after completion of the injection of azoxymethane, Group II (G2) thymoquinone was administered orally at a dose of (50mg/kg) per day until the end of the trial, group III (positive control) was left untreated throughout the study period.Blood samples were taken for biochemical tests on the first day of the experiment, after the injection of azoxymethane was completed, and on the last day of the experiment.Results: the results of the study of biochemical parameters showed vitality. A statistically significant increase (P
Keywords: Colorectal Cancer; thymoquinone; Hepatic enzymes; Rabbits